Parental counseling in trisomy 18: Novel insights in prenatal features and postnatal survival. Issue 2 (16th October 2015) - Russo, Francesca M.; Pozzi, Elisa; Verderio, Maria; Bernasconi, Davide P.; Giardini, Valentina; Colombo, Carla; Maitz, Silvia; Vergani, Patrizia
Abstract : Data on the outcome of trisomy T18 (T18) when diagnosed during pregnancy are lacking. We performed a retrospective study of pregnancies complicated by T18 diagnosed at our center and a literature search for publications on the topic, with pooled estimates of survival rates at different gestational and post‐natal ages. In our series, all the 60 patients included in the analysis had prenatally detected ultrasound anomalies, which were evidenced in the first trimester or at the second trimester scan in 73% of cases. In the continued pregnancies, ultrasound findings did not correlate with prenatal or post‐natal outcome. A meta‐analysis of available literature and our data showed that 48% [37–60%] of fetuses were live born, and among these 39% [11–72%] survived beyond 48 hr and 11% [3–21%] beyond 1 month. Our results confirm that prenatal ultrasound has high sensitivity in detection of T18 but is not predictive of the outcome of the continued pregnancies. The data on survival support that T18, even when antenatally diagnosed, cannot be considered as a uniformly lethal syndrome. © 2015 Wiley Periodicals, Inc.